PENERAPAN GANZE METHOD (METODE GLOBAL) DALAM MENINGKATKAN KUALITAS MEMBACA SISWA DI SEKOLAH DASAR NEGERI 8 BANYUASIN II DESA MUARA SUNGSANG - Mustahang Mustahang; Muhammad Isnaini; Sofyan sofyan; Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
This study aims to 1). Knowing how to apply the Ganze Method (global method) in class II SD Negeri 8 Banyuasin II Muara Sungsang Village 2). Knowing how the reading quality of students before the Ganze Method (global method) was applied in class II SD Negeri 8 Banyuasin II Muara Sungsang Village 3). Knowing how significant the application of the Ganze Method (global method) is in improving the reading quality of students in grade II SD Negeri 8 Banyuasin II Muara Sungsang Village.The type of research used in this research is experimental research using a Posttest-Only Control Design. This study uses a quantitative approach. Furthermore, the data collection method used is the method of observation, interviews, documentation, and tests. And the data analysis technique used the t-test.The results of this study are 1). The experimental class showed that after the Ganze Method (global method) was applied in improving the reading quality of students, the results showed that there were 3 students or (19%) in the high category, 11 students (69%) in the medium category, and 2 students or (12 %) with low category. 2). From the results of the reading scores of students in the control class who did not apply the Ganze Method (global method) in improving the reading quality students, the results showed that there were 2 students or as many as (12.5%) classified as high, 12 students or (75%) classified as moderate, and 2 students or as many as (12.5%) is low. 3). There is a significant difference between the reading quality of the experimental class students who apply the Ganze Method (Global Method) and the control class that does not apply the Ganze Method (Global Method) with the results of the t-test hypothesis: (t0 = 13.61) and the size of